Quantum optimal control in quantum technologies. Strategic report on current status, visions and goals for research in Europe - Koch, Christiane P.; Boscain, Ugo; Calarco, Tommaso; Dirr, Gunther; Filipp, Stefan; Glaser, Steffen J.; Kosloff, Ronnie; Montangero, Simone; Schulte-Herbrüggen, Thomas; Sugny, Dominique; Wilhelm, Frank K. (EPJ quantum technology, 2022)
Quantum optimal control, a toolbox for devising and implementing the shapes of external fields that accomplish given tasks in the operation of a quantum device in the best way possible, has evolved into one of the cornerstones for enabling quantum technologies. The last few years have seen a rapid evolution and expansion of the field. We review here recent progress in our understanding of the controllability of open quantum systems and in the development and application of quantum control techniques to quantum technologies. We also address key challenges and sketch a roadmap for future developments.